A selected review of abstracts from the 19th annual meeting of the Society for Neuro-Oncology. (May 2015) - Chamberlain, Marc C
SUMMARY : The Society for Neuro-Oncology is the largest neuro-oncology meeting in the USA that meets annually and provides a multiday venue presenting new brain cancer clinical trials and basic research data primarily pertaining to gliomas. The Society for Neuro-Oncology 2014 meeting comprising one education day, 3 days of presentation, over 200 oral presentations and 600 abstracts provides a comprehensive overview of neuro-oncology that includes metastatic diseases of the CNS as well as primary brain tumors. This summary attempts to highlight select abstracts presented at this year's meeting in a short review that provides a synopsis of a large and multifaceted meeting.